STRUCTURAL COMPLEXITY OF ARTIFICIAL HABITAT AND THE FEEDING SUCCESS OF PREDATORY DRAGONFLY AND DAMSELFLY - Khairuddin, Lalu Japa dan Nur Lestari (Jurnal Biologi Tropis, 2013)
AbstractThe effect of different habitat complexity structure on the feeding success of predatoryDragonfly and Damselfly over the four of three hours trials was tested using an artificialhabitat complexity structure. Complexity of artificial habitat structure was performed usingwoody bamboo stick of 5 cm in length and 2 mm in diameter. The artificial habitats were setin plastic tank with length and wide of 17 cm and 11.5 cm, respectively and 5.5 cm high. Thedeep of water colom was about 4.5 cm. Preys were larvae of mosquitoes. There was highlysignificant of feeding success of predators in simple structure of habitats and significantenough in complex structure of habitats. In other words, feeding success of predatoryDragonfly and Damselfly was much higher in the simple habitats structure compared to thatof the complex one.Key Words : Artificial Habitat, Damselfly, Dragonfly, Feeding, and PredatoryAbstrakPengaruh kompleksitas struktur habitat terhadap keberhasilan pemangsaan predator Dragonflydan Damselfly selama empat kali tiga jam perlakuan diteliti di laboratorium menggunakanhabitat buatan. Kompleksitas struktur habitat dibuat dengan tongkat dari bambu berukuranpanjang 5 cm dengan diameter 2 mm. Habitat buatan dibuat di bak plastik berukuran panjangdan lebar masing-masing 17 cm dan 11,5 cm, dan tinggi 5,5 cm dengan kedalaman kolom airsekitar 4,5 cm. Larva nyamuk digunakan sebagai pangsa dalam penelitian ini. Setiapperlakuan terdiri dari dua ulangan. Setiap perlakuan berlangsung empat kali masing-masingselama tiga jam. Hasil memperlihatkan, keberhasilan pemangsaan Dragonfly dan Damselflysangat signifikan pada habitat stuktur sederhana, dan cukup signifikan pada habitat yangkompleks. Dengan kata lain, keberhasilan pemangsaan Dragonfly dan Damselfly jauh lebihtinggi pada habitat berstruktur sederhana dibanding dengan pada habitat berstrukturkompleks.Kata Kunci : Damselfly, Draggonfly, Habitat Buatan, Pemangsaan, Pemangsa (Predator)